Transient severe conduction disturbances associated with ankylosing spondylitis. Issue 4 (4th July 2019) - Ikeoka, Kuniyasu; Nishikawa, Nagahiro; Sakakibara, Masayuki; Kawamoto, Keisuke; Hoshida, Shiro
Abstract: A 46‐year‐old man presented with advanced and complete atrioventricular block. He was diagnosed with human leukocyte antigen‐B27‐positive ankylosing spondylitis (AS) and treated with nonsteroidal anti‐inflammatory drugs for AS. The severe atrioventricular block spontaneously improved and resolved after 3 months of therapy. Sequential cardiac magnetic resonance imaging demonstrated transient myocardial high‐intensity signals in the basal septum close to the membranous portion of the septum. A pacemaker was not needed because of the reversible atrioventricular block.